Tahfidzul Qur'an based on Brain Based Learning - Yuike Silvira; Suyadi Suyadi (Edumaspul: Jurnal Pendidikan, 2023)
Countless Muslims who want to memorize the Koran, but they have difficulty, especially easy to forget. There are various methods of memorizing the Qur'an, but only limited to the verses, so they do not understand the meaning. Therefore, a new method is needed to memorize the Qur'an that is easy, both verses and meanings. In addition, there are various methods that can be used to help the process of memorizing the Qur'an at this time, one of which is the brain-based learning method. The purpose of this research is to examine Tahfidzul Qur'an brain-based learning. The approach of this research is qualitative in the description of the library study. The source of data in this study is a study of publications both articles and books in the Google Scholar database with the keyword, "tahfidzul qur'an and brain-based learning". The results prove that to memorize the Koran by using the forebrain as well as the limbic system.